Estudios sobre el justiprecio expropiatorio y el derecho - Vignolo Cueva, Orlando; Vignolo Cueva, Gian Carlo (Revista de Derecho, 2019)
This paper presents and explains some issues of the Peruvian expropriation, trying toinfluence the necessary legal balance that must exist in the treatment and effectivedeployment of this system. In particular, it highlights the acknowledgment by the PeruvianLegislator of a set of guarantees and limits must respect the State (as a whole)and the subject active promoter of the specific procedure. The guarantees available tothe expropriated studied in this article are the valuation and almost forgotten right ofrevertion of the expropriated property.
Keywords: Expropriation; guarantees of expropriated property; right of revertion; valuation; expropriating authority